2014
DOI: 10.1177/2049463714540895
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of chronic non-cancer pain in a UK prison environment

Abstract: Chronic non-cancer pain (CNCP) is significant global health issue, accounting for a substantial increase in prescription analgesics worldwide, in recent decades. This clinical burden is evident in the UK prison population, where the prevalence of CNCP has never previously been determined. This study, conducted in June/July 2013, used prescribing data and a systematic review of clinical records from two UK prison establishments to derive a figure for point-prevalence of CNCP. Results showed that 20% of the tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 29 publications
0
12
0
2
Order By: Relevance
“…This study did not set out to explicitly examine chronic pain and its management in custody, but the narratives provided by participants with chronic pain suggest some dissatisfaction with treatment options in custody. Evidence suggests that a substantial minority of prisoners is affected by chronic pain, and that there is a significant overlap between chronic pain and opioid dependence . For this reason, careful assessment of chronic pain on reception into custody is routinely undertaken and may uncover a history or evidence of aberrant drug using behaviours in some prisoners indicating the presence of a concurrent opioid use disorder for which transfer to OST is best practice management .…”
Section: Discussionmentioning
confidence: 99%
“…This study did not set out to explicitly examine chronic pain and its management in custody, but the narratives provided by participants with chronic pain suggest some dissatisfaction with treatment options in custody. Evidence suggests that a substantial minority of prisoners is affected by chronic pain, and that there is a significant overlap between chronic pain and opioid dependence . For this reason, careful assessment of chronic pain on reception into custody is routinely undertaken and may uncover a history or evidence of aberrant drug using behaviours in some prisoners indicating the presence of a concurrent opioid use disorder for which transfer to OST is best practice management .…”
Section: Discussionmentioning
confidence: 99%
“…Incarceration itself carries substantial risks to health, including a substantially reduced life expectancy [6]. As in this case, chronic pain is a common complaint managed by correctional health clinicians [7].…”
Section: Commentarymentioning
confidence: 99%
“…One study found high rates of severe frequent pain in prisoners 55 years and older, of which a majority received analgesics, including opioids . There are numerous recent publications on pain management at the end of life, focusing on palliative care, and a few empirical studies focusing on specific types of pain (eg, cancer pain or chronic noncancer pain) among prisoners. However, attention to pain management in prison has recently gained some traction, and there have been calls for guidelines in treatment of pain in the prison setting .…”
Section: Introductionmentioning
confidence: 99%